Measurement of the energy density as a function of pseudorapidity in proton-proton collisions at √s=13TeV; European Physical Journal C; Vol. 79, iss. 5 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2019, 2019)
Title screen